2006
DOI: 10.1016/j.bbamcr.2006.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 recognises a specific region in the 3′-UTR of its cognate messenger RNA

Abstract: Annexin A2 is a multifunctional Ca(2+)- and lipid-binding protein. We previously showed that a distinct pool of cellular Annexin A2 associates with mRNP complexes or polysomes associated with the cytoskeleton. Here we report in vitro and in vivo experiments showing that Annexin A2 present in this subset of mRNP complexes interacts with its cognate mRNA and c-myc mRNA, but not with beta(2)-microglobulin mRNA translated on membrane-bound polysomes. The protein recognises sequence elements within the untranslated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 51 publications
4
85
0
Order By: Relevance
“…Therefore, it is possible that AnxA2 plays a role in both localization and/or activation/repression of translation during transport of specific mRNAs, including that of PCSK9. Trans-acting proteins on 3ЈUTR mainly regulate mRNA transport or their stability, whereas those interacting with the 5ЈUTR are mostly involved in initiation of translation (45). Based on RIP assay results, endogenous PCSK9 mRNA in Huh7 cells is coimmunoprecipitated with AnxA2, which supports the hypothesis of PCSK9 regulation through AnxA2 binding with PCSK9 mRNA.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Therefore, it is possible that AnxA2 plays a role in both localization and/or activation/repression of translation during transport of specific mRNAs, including that of PCSK9. Trans-acting proteins on 3ЈUTR mainly regulate mRNA transport or their stability, whereas those interacting with the 5ЈUTR are mostly involved in initiation of translation (45). Based on RIP assay results, endogenous PCSK9 mRNA in Huh7 cells is coimmunoprecipitated with AnxA2, which supports the hypothesis of PCSK9 regulation through AnxA2 binding with PCSK9 mRNA.…”
Section: Discussionsupporting
confidence: 63%
“…These studies identified and suggested a consensus motif 5Ј-AA(C/G)(A/U)G-3Ј that was frequently present in mRNA regions binding AnxA2. AnxA2 is also associated with a subpopulation of messenger ribonucleoprotein complexes (46) and can reduce its own translation (45). Therefore, it is possible that AnxA2 plays a role in both localization and/or activation/repression of translation during transport of specific mRNAs, including that of PCSK9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here annexin A2 functions as a transporter of particular transcription factors and mRNA, to and from the nucleus, respectively (Hollas et al, 2006). In addition, annexin A2 nuclear translocation has been identified as a protective mechanism against DNA-damage (Madureira et al, 2012).…”
Section: Nuclear Annexin A2mentioning
confidence: 99%
“…Similar self-regulatory schemes have been reported for several other RBPs, such as hnRNP M, the sex-lethal protein Sxl, and tra2-␤1; these RBPs bind to their respective cognate pre-mRNAs and influence their splicing (8,21,50). Examples other than splicing factors include the RBP annexin A2, which associates with its cognate mRNA and was proposed to influence its translation (23). Among conventional TTR-RBPs, TTP was shown to bind to and promote the decay of the TTP mRNA, providing a distinct example of a posttranscriptional negative-feedback loop in this protein family (52).…”
mentioning
confidence: 91%